LUNG CANCER IN UKRAINE - Oleksandr I. Vynnychenko; Roman A. Moskalenko; Yuliia V. Moskalenko (Клінічна та профілактична медицина)
Introduction. In 2022, 155,239 new cases of cancer and 84,153 deaths were registered in Ukraine. Among them, lung cancer was diagnosed in 18% of men and 1.4% of women. The study aimed to estimate the incidence of lung cancer in Ukraine and the Sumy region from 2014 to 2023 and to compare it with the indicators of the United States and China.